Care in Translation: Care-ful Research in Medical Settings. Issue 1 (1st March 2020) - Coopmans, Catelijne; McNamara, Karen M.
Abstract: This special issue aims to investigate the possibilities that spring from treating "care" as a practice and a moral-political orientation, through ethnographies and case studies related to medical settings across Asia. It pays attention to who and what is involved in care, and to historical and recent developments that feed into what forms of care are available and how they materialize and are negotiated on the ground. It is also concerned with who or what is produced from specific translations of care: what kind of patient, what kind of action, what sense of place and possibility. Finally, it treats the dilemmas and sense making of researchers regarding the question of how to care as parallel to those of informants or participants, be they patients, medical staff, family members, policy makers, scientists, engineers, activists, and/or others. This "view from Asia" contributes to recent work in STS, anthropology, and feminist studies that in various ways treats care as practice and orientation — namely, by adding a set of situated possibilities for understanding/doing care, place, and scholarly contribution.